A Happy Combination? Great Interests, Particular Interests, and State-Federal Conflicts over Public Lands. Issue 3 (13th April 2018) - Freemuth, John
Abstract: This article analyzes recent developments regarding public lands and their management, focusing on state demands to gain control over federal lands and controversies over national monument designation and the legality of monument reductions. I place recent conflicts over public lands in historical context and show that they are, for the most part, nothing new. Since the 1890s, when the first forest reserves (now national forests) were established, there have been calls to transfer much of the federally managed public lands to states for their management or sell them to private interests. There has also been a century-plus disagreement over natural-resources use versus protection of these same lands. I argue that these conflicts generally follow predictable patterns, while also noting several recent departures from historical patterns.